Flexible Electrodes for In Vivo and In Vitro Electrophysiological Signal Recording. Issue 17 (29th May 2021) - Zhu, Mengjia; Wang, Huimin; Li, Shuo; Liang, Xiaoping; Zhang, Mingchao; Dai, Xiaochuan; Zhang, Yingying
Abstract: A variety of electrophysiological signals (electrocardiography, electromyography, electroencephalography, etc.) are generated during the physiological activities of human bodies, which can be collected by electrodes and thus provide critical insights into health status or facilitate fundamental scientific research. The long‐term stable and high‐quality recording of electrophysiological signals is the premise for their further applications, leading to demands for flexible electrodes with similar mechanical modulus and minimized irritation to human bodies. This review summarizes the latest advances in flexible electrodes for the acquisition of various electrophysiological signals. First, the concept of electrophysiological signals and the characteristics of different subcategory signals are introduced. Second, the invasive and noninvasive methods are reviewed for electrophysiological signal recording with a highlight on the design of flexible electrodes, followed by a discussion on their material selection. Subsequently, the applications of the electrophysiological signal acquisition in pathological diagnosis and restoration of body functions are discussed, showing the advantages of flexible electrodes. Finally, the main challenges and opportunities in this field are discussed. It is believed that the further exploration of materials for flexible electrodes and the combination of multidisciplinary technologies will boost the applications of flexible electrodes for medical diagnosis and human–machine interface. Abstract : Flexible electrodes are important for long‐term, stable, and high‐quality recording of electrophysiological signals. This review summarizes the latest advances in flexible electrodes, including invasive and on‐skin ones, for the acquisition of various electrophysiological signals. The corresponding material selection, the value of the signal acquisition for human health are reviewed. Finally, the challenges and opportunities are discussed.